Basic Accounting for Managerial and Financial Control (Book). - Kam, Vernon; Spiller, Earl A. (The Accounting Review, 1974)
Abstract Reviews the book "Basic Accounting for Managerial and Financial Control," Second Edition by Albert Slavin, Isaac N. Reynolds and John T. Miller.